ROOTSTOCK - example in the french countryside - SUSTAINABLE REVITALISATION IN A RURBAN CONTEXT - Paire, Raphaëlle (My University, 2020)
Located in the geographical centre of France, in what a low-density zone known as the ‘Empty Diagonal’, the city of Guéret suffers from a lack of attractiveness for a few decades. The social and urban changes unbalance the human-scale urban fabric making the historical centre empty. A third of the commercial cells in the city centre are currently vacant, as well as numerous lots of housing there. A loss of identity and unwelcoming atmosphere in the public realm represent the primary issues in this urban context. Despite its negative aspects, Guéret is seen as a lovely historical city with narrow streets, pavements and low-rise buildings made in regional massive stones. The surrounding landscape is largely covered by biodiverse woodlands. The local cultural heritage is also significant due to the local crafts and know-how, the dishes made of agricultural qualitative products. The issue raised in this Master’s Thesis project is a question of the future of a town in a rurban context. Framed within the context of the city centre, the study focuses on how sustainable transformation can be a catalyst for the revitalisation of a city previously abandoned in favour of suburbia and major shopping malls. The Master’s Thesis proposes an enhanced public space design in the city of Guéret, including a new promenade in the historical city centre and the transformation of a group of old residential buildings (and their respective outdoor spaces) into new spatial typologies. The goal of these interventions is to breathe life into the city, improve the sense of local identity and restore interest in the city centre. The project also focuses on social inclusion: how design can improve interaction between active elders, students and youth in order to strengthen community ties. This study may be used as both a reference and a tool for civic associations involved in urban design. Based on an holistic view, the town is considered as a living organism that needs stimulations in specific spaces. The project is led by the assessment on the national phenomena of shrinking cities and by a deep analysis of the city of Guéret.
Keywords: sustainability / human scale / local resources / transformation